M. Raeff, The Well-Ordered Police State. Social and Institutional Change in Germanies and Russia, 1600-1800 - Adam Czarnota (Czasopismo Prawno-Historyczne, 2025)
Recenzja: Marc Raeff, The Well-Ordered Police State. Social and Institutional Change Through Law in Germanies and Russia, 1600 - 1800, Yale University Press, New Haven and London 1983. ss. 284.